STUDY OF THE DEPENDENCE OF THE MODULUS OF ELASTICITY OF A SOLID MATERIAL ON PRISMIC STRENGTH AND DEFORMATION CHARACTERISTICS AT DIFFERENT SOLIDIFICATION TEMPERATURES USING THE BACKWARD ELIMINATION AND LASSO METHODS - Tyrlych, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
This paper presents the results of a comprehensive study of the influence of the physico-mechanical properties of cement stone on its elastic modulus using correlation-regression analysis methods. The research was conducted considering curing temperature regimes simulating real conditions of well cementing in the oil and gas industry. The main focus was on establishing the relationship between prism strength, deformation parameters, and the elastic modulus. For this purpose, three types of regression models were constructed and analyzed: the full model, the simplified model (Backward Elimination), and the Lasso regression model. The application of these approaches allowed not only to identify the key predictors but also to assess their significance under different temperature conditions. Special attention was paid to model diagnostics: testing the normality of residuals, presence of autocorrelation, and heteroscedasticity. Model validation was performed using the coefficient of determination (R²), root mean square error (RMSE), and mean absolute error (MAE). The results demonstrated that prism strength is the primary factor determining the elastic modulus, while deformation parameters have a secondary influence, which increases with temperature rise. This highlights the necessity of considering the temperature factor when predicting the mechanical properties of cement stone. The practical significance of the research lies in the possibility of applying the obtained dependencies to optimize the composition of well cementing slurries, taking into account specific geothermal conditions of wells. This will contribute to enhancing the durability of the cement sheath, reducing the risk of intercolumn flows, and ensuring the integrity of the casing. Thus, the study contributes to the development of predictive methods for the mechanical properties of cement stone and has both theoretical and practical relevance for the oil and gas industry.